2018
DOI: 10.1590/s2175-97902018000100265
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of non-viral gene delivery systems with pEGFP-C1 Plasmid DNA

Abstract: In recent years, non-viral delivery systems for plasmid DNA have become particularly important. They can overcome the disadvantages of viral systems such as insertional mutagenesis and unpredicted immunogenicity. Some additional advantages of non-viral gene delivery systems are; good stability, low cost, targetability, delivery of a high amount of genetic materials. The aim of the study was to develop novel non-viral nanosystems suitable for gene delivery. Two formulations were developed for this purpose: wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Lipoplex-A particle-DNA complexes were found to be of similar size but were notably more heterogenous in shape, with undefined edges. Previous studies have found that nanoparticle shape and size change upon DNA loading, which may be due to complete coating of nanoparticles thus obscuring the edges and giving the lipoplexes a quasi-spherical appearance [14,26]. Lipoplex-A samples also contained small aggregates of DNA visible as smaller particle contaminants in the sample, assumed to be a product of the TEM preparation process, owing to the wetting effect of the hydrophobic grid surface on unbound hydrophilic DNA as previously observed [27].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Lipoplex-A particle-DNA complexes were found to be of similar size but were notably more heterogenous in shape, with undefined edges. Previous studies have found that nanoparticle shape and size change upon DNA loading, which may be due to complete coating of nanoparticles thus obscuring the edges and giving the lipoplexes a quasi-spherical appearance [14,26]. Lipoplex-A samples also contained small aggregates of DNA visible as smaller particle contaminants in the sample, assumed to be a product of the TEM preparation process, owing to the wetting effect of the hydrophobic grid surface on unbound hydrophilic DNA as previously observed [27].…”
Section: Discussionmentioning
confidence: 53%
“…SLN-A particles also demonstrated their ability to bind and protect DNA from DNase degradation. The ability of lipid nanoparticles to protect DNA from nuclease degradation has been documented and is attributed to strong electrostatic interaction with DNA at the particle surface, preventing access to and degradation of bound DNA by nucleases [12,14,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SLNs-based delivery system also has the potential for cellular-based drug directing by altering cellular signaling and gene expression. 58 Besides, SLNs are also deliberated as appropriate substitute carriers for parenteral delivery, 59 gene delivery, 60 pulmonary delivery, 61 and topical and transdermal delivery. 62 , 63 In this review, we will only discuss chemotherapeutic applications.…”
Section: Various Types Of Nanocarrier-based Drug Delivery Systemsmentioning
confidence: 99%
“…SLNak ekoizteko nagusiki erabiltzen diren lipido solidoak[15,16,18]. SLNak ekoizteko nagusiki erabiltzen diren emultsionatzaile eta ko-emultsionatzaileak[15,16,18,[37][38][39][40].…”
unclassified